Perbedaan Keterampilan Proses Sains Siswa Kelas VIII pada Penggunaan Laboratorium Riil dengan Laboratorium Virtual Di SMP Negeri 1 Candi - Faridhotul Khoiriroh; Noly Shofiyah (Proceedings of The ICECRS, 2019)
This study aimed to analyze the differences between students' science process skill in real laboratory and virtual laboratory at SMP Negeri 1 Candi, Sidoarjo. This study was quantitative research with a quasi-experimental design that was conducted at SMP Negeri 1 Candi. The population of this study was 321 students. The sample was selected by purposive sampling considering the equality of ability in the practicum. The Data was collected by using pre-test and post-test. The result revealed that the Fvalue 3,34 < Ftable 3,98 and significant value 0,07 > 0,05, which means there is no difference between student' science process skills in real laboratory and virtual laboratories in SMP Negeri 1 Candi.